Une stratégie multi-échelle pour l’étude paramétrique de détails géométriques au sein de structures en contacts multiples - Boucard, Pierre-Alain; Buytet, Sandrine; Guidault, Pierre-Alain (European Journal of Computational Mechanics, 2007)
This paper presents a multiscale strategy dedicated to the parametric study of structural details inside a structure with multiple friction contacts. The first point of the method uses a micro-macro approach. It is based on a domain decomposition in substructures and interfaces, which involves the resolution of independent “micro” problems in each substructures and transfers the “macro” information only via the interfaces. In a second point, a multiresolution strategy is used in order to reduce the computational cost in the case of problems with design variables. Moreover, the last one consists in modelling the geometry of details without remeshing. On the one hand, it uses a local enrichissement method, the X-FEM, and, on the other hand, level set functions enable one to easily “activate” the detail.